Protection and sustainable use of tropical forests. Points of departure in the Brazilian timber industry - Imme Scholz (Deutsches Institut für Entwicklungspolitik (DIE), 1999)
Protection of tropical forests is essential, for reasons bound up with the need to protect endangered species and the climate. The earth's largest uninterrupted tropical forest is to be found in Brazil's Amazon region. While the dynamics of deforestation has decelerated as compared with the 1970s and 1980s, there is nevertheless no reason to sound the all-clear. The main reasons for the deforestation continue to be cattle-ranching, soybean cultivation, and the logging engaged in by the timber industry.Out of concern about climate change and in the interest of protecting biodiversity, the G7 countries, led by Germany, have, since 1993, made available a total of US 320 million for a pilot program aimed at protecting Brazil's tropical forests (PPG-7). PPG-7 provides for a mixed concept consisting of conservation and environmentally sound agriculture and forestry that is geared to checking the process of deforestation.What this means for the Amazon tropical-timber industry is that it is going to have to convert to sustainable forest management. The industry is in any case under strong pressure to adjust: on the one hand its share of the world timber market is declining because new timber materials are on the advance that offer better technical properties than tropical timber and, since these wood panels are manufactured from timber grown on plantations, are also cheaper. On the other hand the environmentally sensitized sales markets in Europe are demanding more and more certified timber verifiably coming from sustainably managed forests. In this case a reorientation to the more exacting segments of the world market can encourage Brazil's timber industry to adopt production patterns that are more compatible in environmental terms.Development cooperation can contribute to the ecological modernization of the timber industry by supporting Brazil's environmental administration at the regional and municipal levels and providing the firms concerned with assistance in converting to a sustainable forest management. This can take the form of industry-specific consulting programs as well as the development of new intercompany cooperative ventures abroad. Another important approach is to support the marketing of certified timber in Brazil and in Europe alike.
Keywords: 330